Shipwreck of the Kent, ca. 1890 - Gudin, baron, 1802-1880. (1890)
"On the 1st March 1825, the East Indiaman, Kent, met with disaster in the middle of the Bay of Biscay. The ship was bound for Calcutta with 640 people on board, including the right wing of the 31st (Huntingdonshire) Regiment. It was also loaded with 100 tons of shot. During a routine inspection that morning, a cask of rum burst when the ship lurched to one side in rough seas. The crewman went to right it, and dropped his lantern. The spirit ignited instantly and within minutes the ship was alight"--National Maritime Museum Cornwall.
Title devised by cataloguer.
Painting after Incendie du Kent, 1825 by Jean Antoine Théodore de Gudin (1802-1880), painted in 1828.
Also available online
Keywords: Kent (Ship) -- Pictorial works; Cambria (Ship) -- Pictorial works; Shipwrecks -- Biscay, Bay of (France and Spain) -- Pictorial works; Biscay, Bay of (France and Spain) -- Pictorial works